2020
DOI: 10.1111/1751-7915.13630
|View full text |Cite
|
Sign up to set email alerts
|

Field detection of urease and carbonic anhydrase activity using rapid and economical tests to assess microbially induced carbonate precipitation

Abstract: Microbial precipitation of calcium carbonate is a widespread environmental phenomenon that has diverse engineering applications, from building and soil restoration to carbon sequestration. Urease-mediated ureolysis and CO 2 (de)hydration by carbonic anhydrase (CA) are known for their potential to precipitate carbonate minerals, yet many environmental microbial community studies rely on marker gene or metagenomic approaches that are unable to determine in situ activity. Here, we developed fast and cost-effectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Both reactions potentially increase the pH at the biofilm microenvironment—thus, promoting carbonate precipitation—by generating ammonia, in the case of urease, or by increasing the rate of CO 2 degassing, in the case of CA. Using an enzymatic field detection assay (Medina Ferrer et al, 2020), we found in situ active urease and CA in surficial mats from subaqueous tufas (Figure 8a,b; Figure S6). Preliminary assessments in the field showed multiple urease‐positive tufa biofilms in October 2018, which were re‐evaluated and semi‐quantified after a second sampling campaign in August 2020 (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both reactions potentially increase the pH at the biofilm microenvironment—thus, promoting carbonate precipitation—by generating ammonia, in the case of urease, or by increasing the rate of CO 2 degassing, in the case of CA. Using an enzymatic field detection assay (Medina Ferrer et al, 2020), we found in situ active urease and CA in surficial mats from subaqueous tufas (Figure 8a,b; Figure S6). Preliminary assessments in the field showed multiple urease‐positive tufa biofilms in October 2018, which were re‐evaluated and semi‐quantified after a second sampling campaign in August 2020 (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
“…The carbonate samples for microscopic analysis were crushed, homogenized, stained with DAPI (4′,6‐diamidino‐2‐phenylindole), and imaged on an Olympus BX41 microscope (Olympus Corporation). In addition, surficial biofilm samples were also taken in October 2018 from 14 subaqueous tufas and in August 2020 from two subaqueous tufas and from green filaments in the lake water collected adjacent to, but not directly on tufas, and analyzed on‐site to determine urease and carbonic anhydrase (CA) activity (see Section 2.5) using the method described by Medina Ferrer et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations